Pengujian Skala Karamba Jaring Apung Benih F2 Lukas (Puntius bramoides) Produk Pradomestikasi (I): Kualitas Telur, Sintasan Benih dan Kemampuan Memijah - Priyo Susatyo; Sugiharto Sugiharto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
Pre domestication research has been done on fish catches from the Serayu river,  Banyumas, lukas fish (Puntius bramoides) and brek fish (P. orphoides) in natural ponds. The parents as pre domestication product is already successfully demonstrated the ability of adaptive in the new environment in terms of aspects of natural food, has been known to their periodically hormonal profiles, profiles of gametogenesis and spawning capabilities in the new environment (natural pond). Further research aims to determine : (1) The degree of eggs hatching of lukas, (2) survival rate of  F2 seeds and (3) the degree of mortality in the floating net on Serayu river. (4) how long it will take and how the ability of the  post spawning F1 parents to be able to spawn again. Research using survey method. Some units of floating net used for maintenance, testing spawning and growth of parents and seeds of lukas. The results : (1) The degree of eggs hatching between 51%-89%; (2) degree of viability of seeds in floating net  is 54%-92%; (3) while the mortality rate of  seeds 8%-48% and (4) the length of time it takes  male and female parents to reach the next spawning period is ± 6 months. The F1 parents spawn after 6 months on a scale of cages.